The impact of fixed links on population development, housing and the labour market: The case of Norway. (April 2018) - Andersen, Stig Nyland; Díez Gutiérrez, María; Nilsen, Øyvind Lervik; Tørset, Trude
Abstract: This study compares 11 fixed link projects in Norway, linking islands to the mainland. The fixed links substantially increase the accessibility between the islands and the mainland. Thus, interaction between the islands and the mainland increases. Large infrastructure improvements may not only affect the transport patterns but also the population and companies in the connected areas. We apply a difference-in-difference method to analyse the impacts from the increased accessibility. The findings indicate growth in housing prices, population, commuting and employment on the islands. The growth rates of these variables depend on the case characteristics. Urban cases appear to promote larger growth on the island. The contribution of this paper to the literature is that while there have been several studies that have involved single projects, a comparison of several cases that combines assessments of housing and labour markets is still rare in the literature. Highlights: Analysis of housing and labour market and population due to fixed link projects Focus on changes on the islands connected to the mainland. Difference-in-difference method used to quantify impacts. Fixed links promote growth on the connected islands. Fixed links close to cities experience a larger growth than more rural cases.